Multi-Institution Academic Programs: Dealmakers and Dealbreakers - Anderson, Dawn; Moxley, Virginia; Maes, Sue C.; Reinert, Dana (My University, 2009)
Higher education institutions are confronted with increasing demand for electronic access to educational opportunities, improved academic quality and accountability, and new academic programs that address workforce and economic needs. Collaboration allows institutions to combine resources to respond efficiently and effectively to these demands. Universities can bring together their best faculty member(s)with counterparts at similar institutions to rapidly build a new e-learning program that can be offered through each partner institution to a broad audience. The Kansas State University Institute for Academic Alliances (KState IAA) has worked with over 30 multi institution e-learning program start-ups. All of these collaborative initiatives met the K-State IAA criteria for inter-institutional program development, yet some have been wildly successful and others have failed. This paper details some of the reasons for this success (or failure).
Keywords: Great Plains IDEA; Continuing education; Tuition